Leitura do gênero textual policial e estratégias do processo de referenciação - Pelá, Cleuza (2006)
This study, developed as a doctoral thesis in the Program of Post-Graduated Studies in the Portuguese Language at PUC/SP, was conducted in the reading, writing and language teaching research fields and has as its main theme the reading of a specific genre, the detective story, and its processes of referentiation. Based on the hypothesis that, by getting in touch with a specific textual genre, the reader immerses himself in a number of multi-referential webs that arise and transform themselves into language, enabling critical reading on behalf of the reader, we establish as the main aim of this research the proposal of reading strategies that may contribute to the formation of a reader-subject as a social, historical, cultural agent and, as specific aims, to verify: a) if the categories referring to DSG made the constitution of the referentiation process possible, either by means of introducing (new) textual referents, or by anaphorization; b) if the choice of specific textual-linguistic resources contribute to the composition of referential expressions and to the construction of meaning in a text. This research is justified by three reasons: 1st. The reading of the textual detective story genre has become popular in Brazil in the last decades; 2nd. The textual detective story genre has been included in primary and secondary school projects, and even at graduation level; 3rd. there are few works related to the studying of the process of referentiation concerning the textual detective story genre. To give support to the discussion, some concepts such as reading (Compagnon, 2001, 1999; Jouve, 2002), textual genre and textual detective story genre (Albuquerque e Medeiros, 1979; Mandel, 1988; Bakhtin, 2000, 1993; Schneuwly, 2002), referentiation processes (Cavalcante, 2003; Francis, 2003; Koch, 2004, 2002, 1999, 1996 e 1995; Marcuschi, 2000, 1999; Neves, 2000, 1999, 1997), the question-answer-pair (Urbano et al, 2002), among others coming from Socio-Interactionism, Textual Linguistics and the Grammar of the Uses of the Portuguese language have been adopted. The corpus of this study is composed of a number of occurrences of lexical items of the Portuguese language in two detective stories, A Morte no Envelope by Luiz Lopes Coelho and Cabeças de Segunda-feira by Ignácio de Loyola Brandão. For reading this corpus, we proposed, based on the theoretical research, the following strategies: a reading contract, interaction and the collaborative construction of referentiation, which have been applied to each structuring categories of the textual detective story genre. The results allowed us to confirm our hypothesis and to obtain the proposed objectives, as well as to contribute to reading studies and, therefore, providing perspectives to the teaching of the Portuguese language